Systemic Analysis and Violation of the Professional Code of Ethics of Engineers: A Case Study of the PT ITSS Smelter Furnace Explosion Tragedy in Morowali - Taufiqurrahman MG; Eka Daryanto; Syafiatun Siregar (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Indonesia's nickel processing industry plays a strategic role in the global economy, yet fatal occupational safety incidents continue to plague the sector. This study aims to examine in-depth allegations of ethical violations in the PT Indonesia Tsingshan Stainless Steel (ITSS) smelter furnace explosion tragedy in Morowali on December 24, 2023. This study uses a descriptive qualitative method with a case study approach, analyzing secondary data through the lens of the Indonesian Engineers Association (PII) Code of Ethics and the Swiss Cheese Model accident investigation theory. The analysis reveals serious violations of the Catur Karsa principles, particularly the obligation to prioritize public safety. These failures are systemic, involving negligence in risk management, oversight of repair procedures (hot work), and the dominance of production interests over safety. This study recommends reforming the occupational safety and health culture by strengthening the authority of professional engineers and enforcing strict ethical sanctions.